Analisis Pengaruh Kepuasan Pelanggan, Kualitas Produk Milkshake Donut dan Fruit Smoothies Terhadap Word Of Mouth dengan Metode Structural Equation Model (SEM) - Fitriani, Wulan; Hartati, Misra; Nofirza, Nofirza; Nurainun, Tengku (Prodi Teknik Industri Universitas Muhammadiyah Gresik, 2024)
The increasing market competition has impacted customer satisfaction and product quality. A business in the beverage sector experienced a decline in sales, leading to losses. This study aims to analyze the influence of customer satisfaction and product quality of milkshake donuts and fruit smoothies on Word of Mouth (WOM). The company needs to understand the factors affecting customer behavior to improve the effectiveness of their marketing strategies. The method used in this study is Structural Equation Modeling (SEM), which analyzes the complex relationships between these variables. Data were collected through questionnaires distributed to consumers and analyzed using SEM software to test the hypotheses. The results showed that product quality has a significant effect on customer satisfaction. Customer satisfaction also influences WOM, although no direct effect was found between customer satisfaction and WOM. By focusing on improving product quality and customer satisfaction, the company can leverage WOM as an effective promotional tool to strengthen its market position.